Captain Botsis’ Odyssey: On the Biography of the Russian Naval Commander - Yastrebov, Alexey (Quaestio Rossica, 2023)
Referring to archival data of the RGADA (Relations with Venice Fund), this article provides new information about the little-known period of life (1700–1703) of Ivan Botsis related to his transition to the Russian service and directly preceding it. Until now, there is no full-fledged biography of the outstanding associate of Peter the Great, and this study supplements the information about his life full of dangers. Botsis played a significant role in Russia’s success in the Baltic Sea during the Northern War, so filling the gap in his biography is of particular interest. Based on the information introduced into scholarly circulation, the author draws information about his activities immediately after the Morean War (1684–1699). Although he is primarily known as a Russian naval commander, based on the data studied, one may conclude that in his homeland, he proved himself to be a loyal subject of his new homeland, the Venetian Republic, in military affairs. And after the end of the conflict and the conquest of the Peloponnese by Venice, showered with honors, he tried to succeed in a peaceful profession, trading business, and not so much as a merchant but as a coordinator of the commercial activity of his compatriots for private and public benefit. At the peak of his career, the enterprising and even adventurous nature of the Greek captain led him to a conflict with the Venetian and Ottoman authorities, and the hope for the Russian tsar as the deliverer of the Greeks from Turkish rule and sympathy for his military enterprises during the Northern War made him abandon a privileged position in his homeland and embark on a perilous journey to Russia to serve Peter I. The details of his risky escape, described in a petition addressed to the tsar, resemble an excerpt from an adventure novel. The appendix of the article contains previously unpublished documents, i. e. a petition of Captain Botsis and an excerpt of a decree of Tsar Peter on the allocation of his salary.